(untitled) (Innovaciones Educativas, 2025)
The regular practice of reading, known as reading habit, supports both personal and professional development, as it directly impacts individuals’ communication skills and social participation. The development of this habit is linked to factors such as family and academic environments, as well as the discovery of the intrinsic pleasure of reading. This article presents a systematic review of the reading habits of students in secondary and upper secondary education, aiming to analyze the state of research on the topic over the past decade and to describe adolescent reading practices in order to identify patterns and trends relevant for designing action and advocacy strategies. The PRISMA 2020 methodology was used to review 29 empirical studies sourced from open-access databases such as Redalyc and Scielo, as well as subscription-based databases like Academic Search Ultimate and ERIC, to provide a comprehensive and critical overview of the topic. The findings indicate that young people report low frequency and limited time dedicated to reading. Reading for pleasure is infrequent, and many adolescents read only for academic or utilitarian purposes. A significant gender difference was also observed: girls read more than boys and express more positive attitudes toward reading. The study concludes by highlighting the need to explore practices, platforms, and formats that can motivate young people to read and integrate them meaningfully into school contexts.